2017
DOI: 10.1002/hbm.23586
|View full text |Cite
|
Sign up to set email alerts
|

Comparing functional MRI protocols for small, iron‐rich basal ganglia nuclei such as the subthalamic nucleus at 7 T and 3 T

Abstract: The basal ganglia (BG) form a network of subcortical nuclei. Functional magnetic resonance imaging (fMRI) in the BG could provide insight in its functioning and the underlying mechanisms of Deep Brain Stimulation (DBS). However, fMRI of the BG with high specificity is challenging, because the nuclei are small and variable in their anatomical location. High resolution fMRI at field strengths of 7 Tesla (T) could help resolve these challenges to some extent. A set of MR protocols was developed for functional ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 105 publications
2
94
0
Order By: Relevance
“…In line with our findings, (de Hollander et al, 2017) stress that common acquisition parameters (at higher field-strength) may be optimized for specific brain regions and furthermore that brain regions differ in terms of physiological noise contributions and distance from the receiver coils. The authors did not find reliable hemodynamic responses in the brainstem's iron-rich basal ganglia nuclei during a robust stop-signal reaction task using 'standard' 7T imaging parameters.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with our findings, (de Hollander et al, 2017) stress that common acquisition parameters (at higher field-strength) may be optimized for specific brain regions and furthermore that brain regions differ in terms of physiological noise contributions and distance from the receiver coils. The authors did not find reliable hemodynamic responses in the brainstem's iron-rich basal ganglia nuclei during a robust stop-signal reaction task using 'standard' 7T imaging parameters.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have compared 7 T and 3 T fMRI for clinical applications (e.g. (Beisteiner et al, 2011;Morris et al, 2019) or investigated task-evoked activation related to cognition (de Hollander et al, 2017;Theysohn et al, 2013;Torrisi et al, 2018). Yet, only some of these studies have been direct head-to-head comparisons between functional measurements at the two field strengths in the same individuals.…”
Section: Introductionmentioning
confidence: 99%
“…First, an anatomically defined template of the STN region was used to explore how the STN BOLD response relates to SSRT (control) or β (choice uncertainty based on past learning) in the test phase after learning, and in the stop-signal task. The STN template was derived from a recent study using ultrahigh 7 tesla scanning 70 , and selected for its use in previous fMRI studies focusing on reinforcement based conflicted choices 13 , or response inhibition 24,25,28 .…”
Section: Fmri Analysis Procedures and Roi Selectionmentioning
confidence: 99%
“…A probabilistic atlas of a specific ROI can aid optimising the scan sequence for functional imaging studies as it can be used to define the ROI and quantify specific relaxation times. For example, it has been shown that the SNR of an fMRI sequence benefits from a theoretically optimal echo time that is close to the T2* relaxation value of the region of interest (de Hollander et al, 2017). To this end, the atlas of the VTA can be applied to obtain the optimal TE by extracting the T2* values for the VTA from a T2*map.…”
Section: Future Directionsmentioning
confidence: 99%